Is There a “Reverse Causality” from Nominal Financial Variables to Energy Prices? - Santillán-Salgado, Roberto J.; Aali-Bujari, AlÃ; Venegas-MartÃnez, Francisco (International Journal of Energy Economics and Policy, 2019)
This paper is aimed at examining the association between energy prices and financial variables, but, in contrast to previous works, it explores the possibility of a reverse causality from financial variables towards energy prices from a global perspective considering the world’s four largest world economic poles (the United States, China, the European Union, and Japan), as well as the prices of oil (Brent) and Natural Gas. In order to study the interaction between energy prices and relevant nominal variables (stock market returns, interest rates, and exchange rates), a Panel Vector Autoregression Analysis (PVAR) is carried out. The empirical finding is that Brent Oil and Natural Gas price fluctuations are positively and highly significantly influenced by lagged interest rates, that is, energy markets are sensitive to monetary policy signals and, most likely, to economic agents’ expectations about inflation. Other empirical results also reveal that: 1) lagged exchange rate fluctuations have a negative and significant effect over the stock market; 2) a positive performance of the stock market has a negative effect on the exchange rate, and: 3) that interest rate markets follow their own dynamics independently of the rest of the model variables. Keywords: Energy Prices, Stock Market Returns, Interest Rates, Exchange Rates. JEL Classifications: G10, G15, E43, F31 DOI: https://doi.org/10.32479/ijeep.7526